2023
DOI: 10.1097/js9.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of central pancreatectomy in benign or low-grade malignant pancreatic body lesions: a systematic review and meta-analysis

Shiyuan Bi,
Yingyu Liu,
Wanlin Dai
et al.

Abstract: Background: The best approach for treating benign or low-grade malignant lesions localized in the pancreatic neck or body remains debatable. Conventional pancreatoduodenectomy and distal pancreatectomy (DP) are associated with a risk of impairment of pancreatic function at long-term follow-up. With advances in technology and surgical skills, the use of central pancreatectomy (CP) has gradually increased. Objectives: The objective was to compare the safety, feasibility, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…We read with great interest the systematic review and meta-analysis by Bi et al . 1 comparing the safety and efficacy of central pancreatectomy (CP) versus distal pancreatectomy (DP) for benign or low-grade malignant pancreatic body lesions. Their meta-analysis found that CP was associated with longer operative times, greater blood loss, and higher rates of most postoperative complications, including pancreatic fistula, hemorrhage, morbidity, and longer hospital stays than DP 1 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We read with great interest the systematic review and meta-analysis by Bi et al . 1 comparing the safety and efficacy of central pancreatectomy (CP) versus distal pancreatectomy (DP) for benign or low-grade malignant pancreatic body lesions. Their meta-analysis found that CP was associated with longer operative times, greater blood loss, and higher rates of most postoperative complications, including pancreatic fistula, hemorrhage, morbidity, and longer hospital stays than DP 1 .…”
mentioning
confidence: 99%
“…This is an important topic as surgeons continue to debate the appropriate pancreatic parenchymal-sparing operation for small, low-grade pancreatic neck/body lesions. The present investigation included 26 studies comprising nearly 2500 patients, thereby constituting the most extensive examination of the subject to date 1 . The authors are worthy of commendations on the comprehensive analyses.…”
mentioning
confidence: 99%
See 3 more Smart Citations